The Cocorite Shore, Trinidad - (:unkn) unknown (Wilsons Limited, Trinidad, 2009)
The picture show the shore line of Cocorite Bay on the North Western coast of Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fishing villages--Trinidad and Tobago; Coasts--Trinidad and Tobago; Cocorite Bay